Preparation method of thio-spinel composite material and application thereof in aqueous zinc-iodine battery
The thiolated spinel composite material prepared by the bimetallic organic framework precursor synthesis method solves the problem of cation vacancy synthesis, improves the electrochemical performance of aqueous zinc-iodine batteries, and achieves high efficiency, electrochemical stability and rapid ion transport.
Patent Information
- Application Number
- CN202610664256.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-14
- Publication Date
- 2026-08-25
AI Technical Summary
Existing technologies struggle to effectively synthesize thiospinel structures with cation vacancies, and their electrochemical performance in aqueous zinc-iodine batteries needs improvement.
A bimetallic organic framework precursor route was adopted, in which metal salts, bridging ligands and alkalis were reacted in an organic solvent to generate MOF precursors, which were then calcined with sulfur source under an inert atmosphere to form sulfide spinel composite material with iron vacancies. This constructed a nitrogen-sulfur co-doped porous carbon framework, which inhibited the agglomeration of active particles and provided a fast ion transport channel.
The excellent electrochemical performance of thiolated spinel composite material in aqueous zinc-iodine batteries was achieved, exhibiting long cycle life and high rate performance. The self-discharge and polyiodine ion shuttle effect of zinc-iodine batteries were solved, and the initial capacity was high and the structure was stable under high current impact.
Smart Images

Figure CN122638441A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of aqueous zinc-iodine battery cathode materials, and specifically discloses a MOF-derived thiolated spinel composite material containing iron vacancies. Background Technology
[0002] Metal-organic frameworks (MOFs) exhibit significant advantages in the synthesis of bimetallic sulfides due to their highly regular crystal structure and flexibly tunable metal sites. Thanks to their structural characteristics, different metal atoms can be uniformly dispersed in MOF precursors, while organic ligands not only promote the formation of conductive carbon layers during pyrolysis but also effectively inhibit the aggregation of metal sulfide particles. This strategy holds promise for overcoming the limitation of traditional isomorphic ion exchange methods where the precursor and product must maintain the same crystal structure. Recent studies have shown that cation vacancies in host materials can enhance electrochemical performance by modulating electronic structure and promoting electron / ion transport. Specifically, the modulation of electronic structure often involves the movement of transition metal d / p band centers. These modulated electronic orbitals are expected to promote the conversion process of polyiodides, thereby improving the electrochemical behavior of host materials in aqueous zinc-iodine batteries.
[0003] Therefore, we aim to develop a simple synthetic method to prepare FeIn2S4 with cation vacancies in a thiospinel structure and explore its application potential in the cathode of advanced aqueous zinc-iodine batteries. Summary of the Invention
[0004] This invention provides a method for preparing thiospine structured materials with cation vacancies, so as to achieve a simpler synthesis of thiospine composite materials with regular morphology.
[0005] Another object of the present invention is to provide an application of a thiolated spinel structure material with cation vacancies in an aqueous zinc-iodine battery.
[0006] The objective of this application is achieved through the following technical solution:
[0007] A sulfide spinel composite material, wherein the chemical formula of the sulfide spinel composite material is Fe. a In b S c , where 0 < a ≤ 3 / 2, 3 / 2 ≤ b ≤ 5 / 2, 7 / 2 ≤ c ≤ 9 / 2.
[0008] A method for preparing a thiolated spinel composite material includes the following steps:
[0009] (1) Dissolve the indium source and the iron source in an organic solvent to prepare a metal salt solution; dissolve the bridging ligand, modifier, and alkali in an organic solvent to prepare a ligand solution; add the metal salt solution dropwise to the ligand solution to obtain a mixed solution;
[0010] (2) The mixed solution obtained in step (1) is reacted at 100~150℃ for 5~7 hours to obtain the bimetallic In-FeMOF precursor;
[0011] (3) The bimetallic In-Fe MOF precursor obtained in step (2) is mixed with a sulfur source and reacted under an inert atmosphere to obtain the thiolated spinel composite material.
[0012] Preferably, in step (1): the indium source is selected from one or more of In(NO3)3·3H2O, In(NO3)3·4H2O, In(NO3)3·5H2O, and InCl3·4H2O; the iron source is selected from one or more of FeCl3·6H2O, FeCl3·4H2O, and Fe(NO3)3·9H2O; the bridging ligand is 2-aminoterephthalic acid; the modulator is benzoic acid or acetic acid; the alkali is triethylamine or pyridine; and the organic solvent is N,N-dimethylformamide and / or ethanol.
[0013] Preferably, in step (1), the molar ratio of metal ions In:Fe is 1:(0.4-0.5).
[0014] Preferably, the sulfur source in step (3) is thioacetamide or thiourea, and the mass ratio of the bimetallic In-Fe MOF precursor to the sulfur source is 1:4 to 1:20.
[0015] Preferably, in step (3), the calcination temperature is 500~700℃, the heating rate is 2~5℃ / min, the inert atmosphere is argon or nitrogen, and the calcination time is 1~5 hours.
[0016] Furthermore, the nitrogen-sulfur co-doped porous carbon framework generated in situ in the thiositic spinel composite material has a content of 30-40 wt%; the thiositic spinel composite material contains iron vacancies.
[0017] This invention also protects an aqueous zinc-iodine battery, comprising the positive electrode, negative electrode, separator, and electrolyte of the thiosine composite material.
[0018] This invention also protects a positive electrode slurry comprising the thiospinel composite material, elemental iodine, a conductive agent, a binder, and a solvent.
[0019] Furthermore, the positive electrode is made by reacting the thiosine composite material with iodine at a mass ratio of 1:1 to 1:3.
[0020] This invention also protects the application of the thiosine spinel composite material in the preparation of the positive electrode of an aqueous zinc-ion battery.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] By employing a bimetallic organic framework precursor route, molecular-level uniform dispersion of indium and iron atoms is achieved, effectively avoiding the polysulfide phase separation problem caused by crystal structure mismatch in traditional ion exchange methods. During pyrolysis, the organic ligands of the metal-organic framework are transformed in situ into a nitrogen-sulfur co-doped carbon matrix, which not only inhibits the aggregation of active particles but also constructs a unique microrod structure. This structure inherits the morphological characteristics of the precursor, retains abundant porosity between particles, significantly increases the contact interface between the electrode and the electrolyte, and provides a three-dimensional continuous channel for rapid ion transport. Attached Figure Description
[0023] Figure 1 The image shows the XRD pattern of the thiolated spinel composite material of Example 3.
[0024] Figure 2 The image shows the SEM image of the thiolated spinel composite material of Example 3 (scale bar: 2 μm).
[0025] Figure 3 The TEM image of the thiocyanate spinel composite material in Example 3 is shown (scale bar: 1 μm).
[0026] Figure 4 The image shows the long-cycle spectrum of the thiolated spinel composite material of Experimental Example 1 at a current density of 0.2 A / g.
[0027] Figure 5 The image shows the long-cycle spectrum of the thiolated spinel composite material of Experimental Example 1 at a current density of 2 A / g.
[0028] Figure 6 The rate performance spectrum of the thiolated spinel composite material used as the iodine cathode in an aqueous zinc-iodine battery is shown in Experiment Example 2. Detailed Implementation
[0029] The technical solutions of the present invention will be described in detail and comprehensively below with reference to specific embodiments. It should be noted that the provided embodiments represent only a part of the present invention, and not all of it. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0030] Unless otherwise specified, the experimental methods used in the embodiments of this invention are all conventional methods; unless otherwise specified, the materials and reagents used are commercially available reagents and materials, and the commercially available raw materials are used after removing insoluble matter and other impurities by general filtration methods.
[0031] The verification of this embodiment involved testing the electrochemical performance of the prepared positive electrode material by assembling a coin cell. The coin cell model used was 2032. The specific battery preparation and assembly process was as follows: The positive electrode material, conductive agent (Ketjenblack), and binder (PTFE) were mixed uniformly at a mass ratio of 70:20:10. Ethanol was then added to form an electrode sheet using a dry method. The solvent (ethanol) was removed by drying in a 35°C forced-air oven for 15-30 minutes. The dried positive electrode sheet was cut into circular pieces with a diameter of 15 mm. Finally, the prepared positive electrode sheet was assembled into a coin cell with a zinc sheet, a separator (Celgard 2400), and an electrolyte (zinc sulfate electrolyte).
[0032] Example 1
[0033] The thiolated spinel composite material was prepared by a stepwise synthesis method, and the specific steps are as follows:
[0034] 0.463 g of 2-aminoterephthalic acid, 0.08 g of benzoic acid, and 0.4 mL of pyridine were dissolved in 15 mL of N,N-dimethylformamide (DMF). 15 mL of a DMF solution containing 1.406 g of indium nitrate pentahydrate was added dropwise to the above solution. The mixture was transferred to a 50 mL stainless steel high-pressure reactor and heated at 125 °C for 5 h. After the reaction, the yellow product was washed with ethanol and dried at 60 °C to obtain the In MOF precursor.
[0035] The precursor and sulfur source were mixed evenly in a certain proportion, and then calcined at 700℃ under argon protection for 3 hours to obtain the In2S3@C intermediate.
[0036] 0.065 g of In₂S₃ was ultrasonically dispersed in 20 mL of methanol to prepare a 10 mL methanol solution containing 0.028 g of ferrous sulfate and 0.023 g of TAA. The ferrous / TAA solution was added dropwise to the In₂S₃ dispersion, stirred for 10 minutes, transferred to a 50 mL stainless steel reactor, and reacted at 180°C for 18 hours. After washing and drying, the material was calcined at 700°C for 3 hours to obtain the thiolated spinel composite material.
[0037] Example 2
[0038] The thiolated spinel composite material was prepared by a stepwise synthesis method, and the specific steps are as follows:
[0039] 0.293 g InCl3·4H2O and 0.153 g thioacetamide were dissolved in 35 ml of ethanol in a 70% filled polytetrafluoroethylene-lined autoclave. The mixture was subjected to a hydrothermal reaction at 160 °C for 12 h. The mixture was then washed repeatedly with water and ethanol and dried at 75 °C for 12 h to obtain an orange-red powder. Finally, the powder was heat-treated at 500 °C for 3 h in an Ar atmosphere to obtain the indium sulfide precursor.
[0040] 32.6 mg of the previously prepared indium sulfide precursor, metal salt precursor, and thioacetamide (using 29.8 mg of ferric chloride tetrahydrate, 11.3 mg of thioacetamide, and 32.6 mg of indium sulfide) were placed in 35 mL of ethanol and loaded into a polytetrafluoroethylene-lined autoclave at a filling density of 70%. The autoclave was then subjected to a hydrothermal reaction at 180°C for 18 hours. After washing with ethanol and water, the resulting product was freeze-dried for 24 hours and then calcined at 700°C for 3 hours under an argon atmosphere to obtain the thiospine composite material.
[0041] Example 3
[0042] The thiolated spinel composite material was prepared by a one-step synthesis method, and the specific steps are as follows:
[0043] 0.463 g of 2-aminoterephthalic acid, 0.08 g of benzoic acid, and 0.4 mL of pyridine were dissolved in 15 mL of N,N-dimethylformamide. Then, 15 mL of an N,N-dimethylformamide solution containing 0.937 g of In(NO3)3·5H2O and 0.484 g of Fe(NO3)3·9H2O was added dropwise to the above solution. The mixture was transferred to a 50 mL stainless steel high-pressure reactor and heated at 125 °C for 5 h. After the reaction, the orange-red product was washed with ethanol and dried at 60 °C to obtain the In-Fe MOF precursor.
[0044] The precursor and sulfur source were mixed evenly in a certain proportion, and then calcined at 700℃ under argon protection for 3 hours to obtain sulfide spinel composite material.
[0045] Characterization and effect verification
[0046] The morphology of the thiocyanate spinel composite material prepared in Example 3 was characterized by XRD, SEM, and TEM. Figure 1 , Figure 2 , Figure 3 As shown. Test results indicate that the thiocyanate spinel composite material synthesized in Example 3 via a one-step method has a regular rod-like structure.
[0047] The cathode material was prepared using the thiosine spinel composite material obtained in Example 3, and the steps are as follows:
[0048] Weigh 100 mg of thiosine composite material and mix it with iodine at a mass ratio of 1:2. After thorough grinding, transfer the mixture to a polytetrafluoroethylene stainless steel reactor and heat it in an oven to 80°C for 8 hours.
[0049] The battery is assembled using the obtained composite material, and the steps are as follows:
[0050] (1) Weigh the composite material, Ketjen black and polytetrafluoroethylene with a mass fraction of 5% in a ratio of 7:2:1.
[0051] (2) Mix and grind the composite material with Ketjen black for 30 minutes to ensure thorough mixing.
[0052] (3) Weigh out 5% polytetrafluoroethylene and add it to step (2), and continue grinding.
[0053] (4) Press the ground solid mixture evenly onto the conductive mesh.
[0054] (5) Dry the successfully prepared electrode in an oven at 35°C for 20 min.
[0055] (6) Prepare 2 M ZnSO4 electrolyte.
[0056] (7) Using the electrode sheet from step (5) as the positive electrode, the zinc sheet as the negative electrode, a glass fiber separator, and 2M ZnSO4 as the electrolyte, assemble the button cell using conventional methods. The positive and negative electrodes are CR2032 stainless steel casings. After the assembled battery has been left to stand for 2 hours, further electrochemical performance tests are performed.
[0057] Test Experiment Example
[0058] Experimental Example 1: Long Cycle Performance
[0059] The long-cycle performance of the thiocyanate spinel materials in Examples 1, 2, and 3 at 1 C and 10 C rates is shown in the figure below. Figure 4 and Figure 5 As shown.
[0060] The battery with the positive electrode of Example 1 at a current density of 1C has a capacity of 209.9 mAh g. -1 The battery exhibits high initial capacity, with a short-circuit capacity retention of 92.17% after 747 cycles; the positive electrode of Example 2 has a capacity of 195.28 mAh g. -1 The battery exhibits high initial capacity, with a short-circuit capacity retention of 97.01% after 207 cycles; the positive electrode of Example 3 has a capacity of 208.13 mAh g. -1 It has a high initial capacity, and the capacity retention rate is 98.1% after 1000 cycles.
[0061] At a current density of 10C, the battery with the positive electrode of Example 1 has a capacity of 180.76 mAh g. -1 The initial capacity was [not specified], and the short-circuit capacity retention rate after 6700 cycles was 92.4%; at a current density of 10C, the battery with the positive electrode of Example 2 had a capacity of 187.42 mAh g / g. -1The initial capacity was [not specified], and the short-circuit capacity retention rate after 3300 cycles was 89.6%; at a current density of 10C, the battery with the positive electrode of Example 3 had a capacity of 191.8 mAh g / g. -1 It has a high initial capacity, and the capacity retention rate is 94.7% after 20,000 cycles.
[0062] Experimental Example 2: Rate Performance
[0063] Rate performance tests were conducted on the button batteries assembled with thiocyanate spinel materials from Examples 1, 2, and 3. The rate performance spectra of the iodine cathode in the aqueous zinc-iodine battery are shown below. Figure 6 As shown. The thiolated spinel composite material corresponding to Example 3, used as the iodine cathode in an aqueous zinc-iodine battery, exhibited current densities of 0.2 A / g, 0.4 A / g, 1 A / g, 2 A / g, and 4 A / g, respectively. Example 3 showed significantly better capacity retention across the entire rate range compared to Examples 1 and 2, thanks to its optimized material structure, which endowed it with low impedance and rapid charge transport capabilities. When the current density decreased from 4C to 0.2C, the capacity of Example 3 almost recovered without damage, demonstrating that it did not suffer structural damage or irreversible loss of active material under high current impact, indicating excellent mechanical and electrochemical stability. This superior rate performance directly reflects its low internal resistance, high conductivity, and stable interface, laying a core kinetic foundation for achieving ultra-long cycle life at high rates.
[0064] The results show that the thiolated spinel composite material with iron vacancies prepared by the method of this invention, when used as the positive electrode of a zinc-iodine battery and as an iodine host, exhibits excellent long-cycle performance and rate performance, solving the self-discharge problem and the multi-iodine ion shuttle effect faced by zinc-iodine batteries. When applied to aqueous zinc-iodine batteries, the positive electrode based on the thiolated spinel composite material prepared by the one-step synthesis method still maintains 181.6 mAh g⁻¹ after 20,000 cycles. -1 Its high capacity opens up new avenues for the design and development of high-performance aqueous zinc-iodine batteries.
[0065] Obviously, the above embodiments of the present invention are merely examples to clearly illustrate the technical solution of the present invention, and are not intended to limit the specific implementation of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the claims of the present invention should be included within the protection scope of the claims of the present invention.
Claims
1. A sulfide spinel composite material, characterized in that, The chemical formula of the thiocyanate spinel composite material is Fe. a In b S c , where 0 < a ≤ 3 / 2, 3 / 2 ≤ b ≤ 5 / 2, 7 / 2 ≤ c ≤ 9 / 2.
2. A method for preparing a thiolated spinel composite material, characterized in that, Includes the following steps: (1) Dissolve the indium source and the iron source in an organic solvent to prepare a metal salt solution; dissolve the bridging ligand, modifier, and alkali in an organic solvent to prepare a ligand solution; add the metal salt solution dropwise to the ligand solution to obtain a mixed solution; (2) The mixed solution obtained in step (1) is reacted at 100~150℃ for 5~7 hours to obtain the bimetallic In-Fe MOF precursor; (3) The bimetallic In-Fe MOF precursor obtained in step (2) is mixed with a sulfur source and reacted under an inert atmosphere to obtain the thiolated spinel composite material.
3. The preparation method according to claim 2, characterized in that, In step (1): the indium source is selected from one or more of In(NO3)3·3H2O, In(NO3)3·5H2O, and InCl3·4H2O; the iron source is selected from one or more of FeCl3·6H2O, FeCl3·4H2O, and Fe(NO3)3·9H2O; the bridging ligand is 2-aminoterephthalic acid; the modulator is benzoic acid or acetic acid; the alkali is triethylamine or pyridine; and the organic solvent is N,N-dimethylformamide and / or ethanol.
4. The preparation method according to claim 2, characterized in that, In step (1), the molar ratio of metal ions In:Fe is 1:(0.4-0.5).
5. The preparation method according to claim 2, characterized in that, The sulfur source in step (3) is thioacetamide or thiourea, and the mass ratio of the bimetallic In-Fe MOF precursor to the sulfur source is 1:4 to 1:
20.
6. The preparation method according to claim 2, characterized in that, In step (3), the calcination temperature is 500~700℃, the heating rate is 2~5℃ / min, the inert atmosphere is argon or nitrogen, and the calcination time is 1~5 hours.
7. The preparation method according to claim 6, characterized in that, The nitrogen-sulfur co-doped porous carbon framework generated in situ in the thiocyanate spinel composite material has a content of 30-40 wt%.
8. An aqueous zinc-iodine battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that, The positive electrode contains the thiospinel composite material as described in claim 1.
9. The aqueous zinc-iodine battery according to claim 8, characterized in that, The positive electrode is made by reacting the thiosine composite material with iodine at a mass ratio of 1:1 to 1:
3.
10. The application of the thiosine spinel composite material according to claim 1 in the preparation of the positive electrode of an aqueous zinc-ion battery.